PENGARUH PERSEPSI TERHADAP KESEJAHTERAAN GURU PAUD DENGAN MINAT MENJADI GURU PADA MAHASISWA PG PAUD FIP UNNES - Susiani, Ida (Jurusan PGPAUD FIP UNNES, 2013)
Perception is a process of concluding observations obtained with the information and interpret the message through the five senses into an understanding that became the basis for the experience and knowledge. Welfare is a condi tion where a person feels safe, prosperous and can meet the needs of social life along with the appreciation of where he lived. Interest is essentially a preferred taste and sense of belonging to a thing or event, with no one telling. This research aimed to describe the relationship and influence positive and significant correlation between perceptions of early childhood teachers with an interest in the welfare of a student teacher in early childhood UNNES. The population of this research is a student of early childhood FIP 2008-2011 UNNES total 171 students. This research is descriptive quantitative. The analysis method used is descriptive percentages with simple regression analysis. The results of the analysis obtained value R of 0.729 with a significance level of 0.005 means that the welfare of teachers' perceptions with a teacher interest in early childhood education students UNNES ties. Perceptions welfare of teachers with interest of a teacher having a significant effect, with a value of 53.2% R square means to influence the perception welfare of teachers with an teacher interest of a student early childhood teachers on UNNES influenced by 53.2% and the remaining 46.8 % influenced by other factors. Based on these results it can be concluded that teachers' perceptions of well-being has a positive and significant effect on interest in becoming a teacher. Therefore, if the view of the welfare of a more early childhood teachers raised again the interest of students to become teachers will also rise. So students are advised to pay more attention to the welfare of early childhood teachers working in early childhood education where the institution is more advanced / large (urban areas) and if only their salary is much larger than the early childhood small institution (rural area). With the view that teachers welfare early childhood teachers working in early childhood are more advanced / large is the interest to be early childhood teachers on individual self will increase. Because students will be held that will eventually become early childhood teachers then his life will prosper.